STRATEGI PEMERINTAH RIAU DALAM MENINGKATKAN INVESTASI ASING DI PROVINSI RIAU - Heryansyah, Tengku Rizki; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The objective of this thesis is to understand the extent of the Riau Provincial Government's strategies aimed at enhancing investment. The growth of investment, encompassing both Domestic Investment (DCI) and Foreign Direct Investment (FDI), is undoubtedly linked to the economic advancement of the region, specifically Riau Province. However, the absence of a robust and transparent policy framework poses a challenge in attracting sufficient investment to Riau Province. While the quantitative investment rate has experienced an upsurge, the lack of comprehensive legal safeguards can be a concern. Besides quantitative factors, various other aspects converge in the realm of investment, including institutional dynamics, policy formulation, tax certainty, licensing procedures, and political stability. This research employs a descriptive approach, collecting data through case studies from the literature. The foreign direct investment theory and the perspective of economic liberalism are harnessed to analyze the strategies implemented by Riau's government for fostering investment in the province. The utilization of these theories and concepts aids in comprehending the government's strategies more effectively. The findings of this research indicate that the impediments to increased investment encompass several aspects, such as insufficiently skilled human resources, budgetary constraints, limited coordination both horizontally and vertically among institutions, and inadequate implementation of technology and information systems. To ensure a conducive investment climate, the Riau provincial administration must further enhance its efforts, particularly as the current infrastructure in Riau necessitates improvements, particularly in terms of specialized company transportation networks. Keywords:strategy,investation,promoti.